2018
DOI: 10.18203/2320-6012.ijrms20184405
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the adult human dry hip bone in Kashmiri population

Abstract: Background: The distinctive morphology of the human hip bone makes it of interest from anatomical, anthropological and forensic point of view. Thus, by using visual criteria, metric techniques and discriminant function analysis we can estimate the age, sex and race of an individual. Objective was to do the morphometry of 60 dry human hip bones in Kashmiri population in order to evaluate the various parameters of the hip bone.Methods: The study was done on 60 randomly collected Kashmiri adult unpaired hip bones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The coxal Index was 74.59 on the right side and 73.32 on the left side (nayak et al, 2017). They found out that there was more strength of the skeletal element on the right hip bone (Kausar et al, 2018). based on our study it was found that the average diameter of male was 48.70 and the average diameter of females was 46.38.…”
Section: Resultssupporting
confidence: 49%
“…The coxal Index was 74.59 on the right side and 73.32 on the left side (nayak et al, 2017). They found out that there was more strength of the skeletal element on the right hip bone (Kausar et al, 2018). based on our study it was found that the average diameter of male was 48.70 and the average diameter of females was 46.38.…”
Section: Resultssupporting
confidence: 49%
“…Morphometric studies require measurements of the hip bone in a standard position for consistency and reproducibility. We could not reach sufficiently detailed and confidently reproducible position descriptions for morphometric measurements of an irregular bone such as coxal bone (10,(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The distance between the lowest point of the ischial tuberosity and the highest point of the iliac crest was measured for height. The distance between the anterior superior iliac spine and posterior superior iliac spine was measured for width (10).…”
Section: General Morphometric Measurements Of the Coxal Bonesmentioning
confidence: 99%